(untitled) (The Review of Diabetic Studies, 2025)
This quasi-experimental study assessed the impact of Cognitive Behaviour Therapy (CBT) on the quality of life among depressive patients admitted in selected hospitals in Indore, Madhya Pradesh. A total of 176 participants were selected, and pre-test and post-test assessments were conducted using standardized scales measuring quality of life, depression symptoms, and CBT adherence. The findings revealed significant improvements in all four domains of quality of life—physical, psychological, social, and environmental—following the CBT intervention. Depression symptoms showed a substantial reduction across all items, including mood disturbances, sleep problems, anhedonia, fatigue, and feelings of worthlessness. The CBT adherence data indicated high participant engagement, reflected in consistent homework completion, the use of cognitive restructuring, behavioral activation, and confidence in utilizing therapy strategies independently. The overall results demonstrate that CBT is an effective therapeutic modality for enhancing well-being and reducing depressive symptoms among hospitalized patients. The study highlights the importance of incorporating CBT into routine psychiatric treatment to promote long-term recovery and improved quality of life.